2019
DOI: 10.3354/aei00300
|View full text |Cite
|
Sign up to set email alerts
|

Anti-predator response of Haliotis tuberculata is modified after only one generation of domestication

Abstract: Domestication of Haliotis tuberculata has only recently begun. During the process, we expect that behavioural and physiological traits may evolve to become more adapted to their captive environment. These modifications may result from intentional selection of production traits or unconscious and unintentional selection due to conditions experienced in the farm environment. To study this process at the earliest stage, the progeny of 3 different broodstocks obtained from wild parents, selected farmed abalone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
(75 reference statements)
2
7
0
Order By: Relevance
“…The behavioural responses were qualitatively similar and were consistent with previously reported stereotypical behaviours (e.g. mucus ejection followed by an evasive move away from the contact area) (Bullock, 1953;Feder, 1963;Parsons and Macmillan, 1979;Day et al, 1995;Bancalà, 2009;Roussel et al, 2019). When the mucus is ejected, it drifts through the water and carries the smell of abalone and the starfish may therefore be unable to detect the abalone position (Day et al, 1995).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
See 2 more Smart Citations
“…The behavioural responses were qualitatively similar and were consistent with previously reported stereotypical behaviours (e.g. mucus ejection followed by an evasive move away from the contact area) (Bullock, 1953;Feder, 1963;Parsons and Macmillan, 1979;Day et al, 1995;Bancalà, 2009;Roussel et al, 2019). When the mucus is ejected, it drifts through the water and carries the smell of abalone and the starfish may therefore be unable to detect the abalone position (Day et al, 1995).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
“…The domestication of most abalone species has begun recently (Roussel et al, 2019), and only a few studies have characterized the potential effects of domestication on abalone behaviours. Lachambre et al (2017 a) reported that three-year-old hatchery-reared H. tuberculata exhibited fewer reactions to stimulation of their foot compared to wild specimens.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that when both shelter and food were provided, the abalones more actively foraged at higher temperature than at lower temperature, which was not the case with hiding behavior. This can be considered as a decision of the abalone based on the trade-off between feeding and predation escape behaviors (Roussel et al 2019). Food availability and satiation can influence the hiding behavior of abalones.…”
Section: Discussionmentioning
confidence: 99%
“…These hiding and foraging behaviors are important for their survival and growth because they reduce the risk of predation and increase food consumption. Although abalones can detect predators by chemosensory and tactile cues (Hansen and Gosselin 2016;Roussel et al 2019), light is the basic trigger that induces hiding and foraging (Gorrostieta-Hurtado and Searcy-Bernal 2004;Pereira et al 2007;Searcy-Bernal et al 2003). We hypothesized that foraging and hiding behaviors of juvenile H. discus hannai would be enhanced by temperature increase.…”
Section: Introductionmentioning
confidence: 99%